SPACES WITH LIMIT OPERATION - Atabekian, V. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
In this work the space (X, Λ) with limit operation (constracted by I. G. Khachatryan) is studied with the help of non-standard models. With the help of non-standard extentions are described the complete systems of neighbourhoods of (X, Λ), the open and closed sets, the convergence, the limit points of the set, the spaces as well as separation spaces.
Keywords: limit operation; non-standard extentions; limit points of the set